Innovation of Pindang Muara Enim: Analysis of Consumer Acceptance and Marketing Strategies for Culinary Tourism Development : JEL Classification: M31, L83, O31, Q13, Z32 - Kartika Theresia Simangunsong; Rizka Yuniarti; Pelliyezer Karo Karo (Newinera Publisher, 2026)
The purpose of this study was to develop and test the initial consumer acceptance of the innovation of Muara Enim pindang using kemang fruit instead of the traditional souring agents like tamarind and pineapple. This research used a Research and Development model with a focus on product testing. The study used a questionnaire with 93 consumers in South Sumatra who were familiar with pindang. Product acceptance was evaluated using organoleptic characteristics including colour, aroma, texture and taste in three parts of the product: fish part, soup and seasonings. Descriptive and Net Promoter Score (NPS) analysis were applied to determine the acceptance, promotion, and attributes that needed improvement. This study shows the innovation was welcomed, with a total NPS score of +30. The highest scored attributes are broth taste (NPS score of +59), fish component taste (+55) and broth texture (+55), which means that the primary sensory aspects of the innovation were accepted by consumers. But, the taste of condiment, taste of fish component, and texture of condiment are lower, indicating that there is potential to improve the visual appearance and supporting components. The socio demographic profile of the respondents also shows that millennials and Generation Z are the potential consumers, with family oriented visits and growing digital payment. The results suggest that the innovation of Muara Enim pindang has a potential as local gastronomic product, but needs improvement to enhance sensory integrity and consumer acceptance. The research suggests enhancing visual attributes, focusing on taste consistency, and marketing approaches that combine local identity, family and digital trends..